Mutation signatures in head and neck squamous cell carcinoma : Pathogenesis and therapeutic potential - Plath, M; Hess, J; Zaoui, K (HNO, 2020)
The pathogenesis of head and neck squamous cell carcinoma (HNSCC) is a complex and multistage process which results from the interaction of exogenous and endogenous cellular processes. Each of these processes leaves a characteristic pattern of mutations on the tumor genome, a so-called mutational signature. The subject of current studies is to decipher specific signatures of mutational processes operating during HNSCC pathogenesis and to address their prognostic value. Computational analysis of genomic sequencing data by The Cancer Genome Atlas (TCGA) revealed mutational signatures 1, 2, 4, 5, 7, and 13 as the main players in HNSCC pathogenesis. Signature 16 was first discovered in human papillomavirus (HPV)-negative oral and oropharyngeal tumors. In many studies, an association of signature 16 with alcohol and tobacco consumption as well as with an unfavorable prognosis was described.